Improving transparency to build trust in real‐world secondary data studies for hypothesis testing—Why, what, and how: recommendations and a road map from the real‐world evidence transparency initiative. Issue 11 (13th September 2020) - Orsini, Lucinda S.; Monz, Brigitta; Mullins, C. Daniel; Van Brunt, David; Daniel, Gregory; Eichler, Hans‐Georg; Graff, Jennifer; Guerino, John; Berger, Marc; Lederer, Nirosha M.; Jonsson, Pall; Schneeweiss, Sebastian; et al.
Abstract: Real‐world data (RWD) and the derivations of these data into real‐world evidence (RWE) are rapidly expanding from informing healthcare decisions at the patient and health system level to influencing major health policy decisions, including regulatory approvals and coverage. Recent examples include the approval of palbociclib in combination with endocrine therapy for male breast cancer and the inclusion of RWE in the label of paliperidone palmitate for schizophrenia. This interest has created an urgency to develop processes that promote trust in the evidence‐generation process. Key stakeholders and decision‐makers include patients and their healthcare providers; learning health systems; health technology assessment bodies and payers; pharmacoepidemiologists and other clinical reseachers, and policy makers interested in bioethical and regulatory issues. A key to optimal uptake of RWE is transparency of the research process to enable decision‐makers to evaluate the quality of the methods used and the applicability of the evidence that results from the RWE studies. Registration of RWE studies—particularly for hypothesis evaluating treatment effectiveness (HETE) studies—has been proposed to improve transparency, trust, and research replicability. Although registration would not guarantee better RWE studies would be conducted, it would encourage the prospective disclosure of study plans, timing, and rationale for modifications. A joint task force of the International Society for Pharmacoeconomics and Outcomes Research (ISPOR) and the International Society for Pharmacoepidemiology (ISPE) recommended that investigators preregister their RWE studies and post their study protocols in a publicly available forum before starting studies to reduce publication bias and improve the transparency of research methods. Recognizing that published recommendations alone are insufficient, especially without accessible registration options and with no incentives, a group of experts gathered on February 25 and 26, 2019, in National Harbor, Maryland, to explore the structural and practical challenges to the successful implementation of the recommendations of the ISPOR/ISPE task force for preregistration. This positioning article describes a plan for making registration of HETE RWE studies routine. The plan includes specifying the rationale for registering HETE RWE studies, the studies that should be registered, where and when these studies should be registered, how and when analytic deviations from protocols should be reported, how and when to publish results, and incentives to encourage registration. Table 1 summarizes the rationale, goals, and potential solutions that increase transparency, in addition to unique concerns about secondary data studies. Definitions of terms used throughout this report are provided in Table 2.